1994
DOI: 10.1007/bf00227282
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular and somatosensory contributions to responses to head and body displacements in stance

Abstract: The relative contribution of vestibular and somatosensory information to triggering postural responses to external body displacements may depend on the task and on the availability of sensory information in each system. To separate the contribution of vestibular and neck mechanisms to the stabilization of upright stance from that of lower body somatosensory mechanisms, responses to displacements of the head alone were compared with responses to displacements of the head and body, in both healthy subjects and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
0
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(109 citation statements)
references
References 40 publications
6
99
0
4
Order By: Relevance
“…Previous work with other senses has shown that it is common for different sensory modalities to interact non-linearly (Horak et al 2001;Li et al 1999;Shimojo and Shams 2001). In a system where multiple sensory modalities are involved in control, if one modality is lost, disrupted or unreliable, remaining functional modalities can be reweighted (Horak et al 1994). These same types of interactions in the phonatory control system could allow the weighting of different sensory modalities to be modified to obtain optimal regulation of voice F 0 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work with other senses has shown that it is common for different sensory modalities to interact non-linearly (Horak et al 2001;Li et al 1999;Shimojo and Shams 2001). In a system where multiple sensory modalities are involved in control, if one modality is lost, disrupted or unreliable, remaining functional modalities can be reweighted (Horak et al 1994). These same types of interactions in the phonatory control system could allow the weighting of different sensory modalities to be modified to obtain optimal regulation of voice F 0 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we think that change of head movement occurred. Head movements and corresponding vestibular input influence postural response 21) . In the case of repeated perturbation to seated subjects' trunks, the subjects attenuated their neck muscle activity and modulated their head movement 22) .…”
Section: Discussionmentioning
confidence: 99%
“…Standing posture, for example, is affected by perturbations of visual, vestibular and proprioceptive sensory systems. [31][32][33] The specific role of the basal ganglia in postural control is complex and only beginning to be unraveled but is believed to be involved in several functions, including: (1) sensory channel integration; (2) selection of automatic postural reactions generated in response to motor and sensory perturbations, e.g. moving visual environments; (3) motor control flexibility and adaptability, i.e.…”
Section: Locomotor and Postural Control Centersmentioning
confidence: 99%